Influence of curve fitting techniques on hydrostatic characteristics of ship (Journal of Mechanical Engineering, 2009)
This paper presents influence of curve fitting techniques on hydrostatic characteristics of marine vessels.Â  Three vessels having lengths of 32.16m, 70.0m and 25.6m are selected for this study. The hull geometries of these vessels are represented by three curve fitting techniques such as least square, cubic spline and B-spline methods. At first, hydrostatic characteristics of the vessels are calculated using data only available in offset table and then using more data generated by curve fitting techniques. Finally, results obtained by offset table data are compared to those by fitted data. It is seen that there are some influences of curve fitting technique on the hydrostatic characteristics of ship especially at lightly loaded condition. Keywords: Curve fitting technique, ship hull form, offset table, hydrostatic characteristics, ship stability, cross curve. doi:10.3329/jme.v39i2.1853 Journal of Mechanical Engineering, Vol. ME39, No. 2, Dec. 2008 100-112